Outcomes of Covid-19 on Nasal Disorders and Assessment of Quality of Life in Post-Covid Patients. - Dr. Mudhar Hameed Rasheed; Dr. Ali Hussein Ali Saeed; Dr. Mahmood Sami Wafeeq (Zien Journals, 2022)
Studies and discussions about different forms of presentation began to spread COVID-19 and its consequences and effects, including olfactory imbalances such as sleep disturbances, anxiety and depression, activity, and breathing.
Keywords: Covid-19; Nasal disorders; Arterial hypertension; Diabetes